Urgensi E-Marketing Berbasis Google Maps pada Keberlangsungan Usaha Entrepreneur Muslim (Studi pada Kabupaten Demak) - Bayu Tri Cahya; Etha Widyarani; Farida Rohmah; Makrufah Hidayah Islamiah (Kompartemen : Jurnal Ilmiah Akuntansi, 2022)
The digital world is predicted to be a crucial point for all human activities, including business activities. Some indicators that can be used today include the increase in expenditure on digital advertising, the growth in the use of smartphones that provide easy internet access. This article analyzes the implementation of the emergence of new entrepreneurs who use the digital world as a form of electronic marketing (e-marketing). This research approach uses a phenomenological approach, in the context of qualitative research. The researcher measures as a facilitator who contributes to the reality constructed by the subject of the research. The purpose of this article is the urgency of implemention Google Maps for sustainable business. The results of this research evidence that the implementation of e-marketing based on Google maps conducted by Muslim entrepreneurs has a positive impact on the increase of income and the role of technology that facilitates and insure the sustainability of Muslim Entrepreneurs because it is appropriate with the concept of the industrial revolution 4.0.